A call for action: Improve reporting of research studies to increase the scientific basis for regulatory decision‐making. Issue 5 (3rd January 2018) - Ågerstrand, Marlene; Christiansen, Sofie; Hanberg, Annika; Rudén, Christina; Andersson, Lars; Andersen, Sjur; Appelgren, Henrik; Bjørge, Christine; Clausen, Ian Henning; Eide, Dag Markus; Hartmann, Nanna B.; Husøy, Trine; et al.
Abstract: This is a call for action to scientific journals to introduce reporting requirements for toxicity and ecotoxicity studies. Such reporting requirements will support the use of peer‐reviewed research studies in regulatory decision‐making. Moreover, this could improve the reliability and reproducibility of published studies in general and make better use of the resources spent in research. Abstract : This is a call for action to scientific journals to introduce reporting requirements for toxicity and ecotoxicity studies. Such reporting requirements will support the use of peer‐reviewed research studies in regulatory decision‐making. Moreover, this could improve the reliability and reproducibility of published studies in general and make better use of the resources spent in research.